Pengaruh Penetration Pricing Dan Peningkatan Motivasi Konsumen Terhadap Keputusan Pembelian Mi Konyol Bumiayu - Sarah Dien Hawa; Mia Anjani (Universitas Kristen Indonesia Toraja, 2023)
MSMEs have contributed 60.34% of Indonesia's gross domestic product (GDP). This number is spread throughout Indonesia. MSMEs have a very important role in the economic sector in Indonesia. Bumiayu's konyol noodle SMEs in the last 1 year decreases their sales because of Indonesia's economic situation which has not fully recovered after the co-19 disaster. The demand for konyol noodles has decreased in the last year due to rising prices of raw materials and supporting materials and also because of increasing fuel prices. This study analyzes the effect of penetration pricing and consumer motivation on purchasing decisions for Bumiayu’s konyol noodle. A sample are 97 respondents who have used MSME products at least twice, was tested using a questionnaire and analyzed through multiple linear regression. The result is that penetration pricing and consumer motivation have a positive effect on purchasing decisions for Bumiayu silly noodle products. The implications of the results of this study are as a basis for determining strategies that can increase sales and profits of mi konyol Bumiayu.